International Legal Regulation of Counter-Terrorism in Peacetime and During the Armed Conﬂicts: a regional approach of the Commonwealth of Independent States - I. I. Коtlyarov; Yu. V. Puzyreva (Московский журнал международного права, 2022)
INTRODUCTION. The increase in the number of armed conﬂicts involving non-State armed groups recognized as terrorist in States and international organizations has been the trend in recent years. In this regard, the question relating to the links between terrorism and armed conﬂict, as well as between the international legal regulation of combating terrorism and international humanitarian law, is on the agenda. The article examines the regional approaches of the CIS to countering terrorism within armed conﬂicts and during counter-terrorism operations in peacetime.MATERIALS AND METHODS. The material for the research included the universal treaties, the model legislation of the CIS on IHL and in the ﬁeld of combating terrorism, as well as the conceptual documents of the military-strategic cooperation of the CIS member states in particular in identifying areas and forms of countering international terrorism as a modern military threat. The methodological basis of the research included general scientiﬁc and private scientiﬁc methods of cognition traditional for legal researches.RESEARCH RESULTS. The research substantiates the hypothesis that within the Commonwealth there were formed the legal regimes, which are based on the generally recognized principles and norms of international law governing the issues of military counteraction to terrorist threats both in peacetime and during armed conﬂicts. The article analyzes international treaties, model legislation of the CIS and national legal acts of the member states establishing the legitimacy of military methods and means of response to terrorist challenges and threats within the special legal regime of the "counter-terrorist operation". A relevant aspect of the study was the identiﬁcation of the prospects of military cooperation between the CIS member states through the development of new mechanisms for combating terrorism– "military-police operations" in the system of their joint counter-terrorism activities.DISCUSSION AND CONCLUSIONS. In modern realities, it is the most eﬀective to build the counteraction to terrorism within the CTO legal regime which enable to combine law enforcement and military tasks faced by the state within ensuring its internal and external security, and also contains guarantees for ensuring and protecting human rights. Meanwhile, the involvement of the armed forces of the state in combating terrorism does not mean an unequivocal transfer of the situation from peacetime to the regime of martial law. The CIS, conscientiously fulﬁlling its obligations under the key acts of IHL, has set out in its model legislation the norms prohibiting terrorism during armed conﬂicts and establishing responsibility for acts of its. In addition, under the auspices of the CIS there has been developed and successfully implemented the model legislation regulating the use of military methods and means of response to terrorist challenges and threats within a special legal regime of a “counter-terrorism operation” separated from the regime of the use of armed forces within the IHL.